India after Gandhi : the history of the world's largest democracy - Guha, Ramachandra (New York, NY : Ecco, an imprint of HarperCollinsPublishers, 2019)
Born in privation and civil war, divided by caste, class, language and religion, independent India emerged, somehow, as a united and democratic country. This book tells the full story, the pain and the struggle, the humiliations and the glories, of the world's largest and least likely democracy. The author, a social historian writes of the protests and conflicts that have peppered the history of free India, but also of the factors and processes that have kept the country together (and kept it democratic), defying numerous prophets of doom who believed that it would break up or come under autocratic rule. This story of modern India is peopled with extraordinary characters: the author gives fresh insights on the lives and public careers of the long-serving prime ministers, but also writes about the major provincial leaders and other lesser known (though not necessarily less important) Indians, peasants, tribals, women, workers and musicians.
Preface to the second edition -- Prologue: Unnatural nation -- Part 1: Picking up the pieces. Freedom and parricide ; The logic of division ; Apples in the basket ; A valley bloody and beautiful ; Refugees and the Republic ; Ideas of India -- Part 2: Nehru's India. The biggest gamble in history ; Home and the world ; Redrawing the map ; The conquest of nature ; The law and the prophets ; Securing Kashmir ; Tribal trouble -- Part 3: Shaking the centre. The southern challenge ; The experience of defeat ; Peace in our time ; Minding the minorities -- Part 4: The rise of populism. War and succession ; Leftward turns ; The elixir of victory ; The rivals ; Autumn of the matriarch ; Life without the Congress ; Democracy in disarray ; This son also rises -- Part 5: A history of events. Rights and riots ; A multi-polar polity ; Rulers and riches ; Progress and its discontents ; The rise of the "BJP system" -- Epilogue: A 50-50 democracy.
"Revised and updated"--Cover.
Includes bibliographical references (pages 787-881) and index
Keywords: Since 1947; India -- History -- 1947-; India; History